Diethylstilboestrol for the treatment of prostate cancer: past, present and future. (February 2014) - Turo, Rafal; Smolski, Michal; Esler, Rachel; Kujawa, Magda L.; Bromage, Stephen J.; Oakley, Neil; Adeyoju, Adebanji; Brown, Stephen C. W.; Brough, Richard; Sinclair, Andrew; Collins, Gerald N.
Abstract: The aim of this review was to discuss the most recent data from current trials of diethylstilboestrol (DES) to identify its present role in advanced prostate cancer treatment as new hormonal therapies emerge. The most relevant clinical studies using DES in castration-refractory prostate cancer (CRPC) were identified from the literature. The safety, efficacy, outcomes and mechanisms of action are summarized. In the age of chemotherapy this review highlights the efficacy of oestrogen therapy in CRPC. The optimal point in the therapeutic pathway at which DES should be prescribed remains to be established.